ENDOMETRIOID ENDOMETRIAL CARCINOMA: AN INSTITUTIONAL CASE SERIES - K T ATHULYA KRISHNA KUMAR (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: To present a case series of endometrioid endometrial carcinoma having diverse presentations, histopathological features, and therapeutic modalities. Methods: A case series of five cases of histopathologically diagnosed endometrioid endometrial carcinoma in a tertiary care center has been presented. Cases were collected over a period of 8 months (April 2017–December 2017). Results: The ages of the patients ranged from 48 to 67 years. All patients were post-menopausal and one patient was pre-menopausal. In histopathology, there were two cases of grade 1, two cases of grade 3, and a single case of grade 2. FIGO staging of the cancers ranged from stage I to stage IIIc and appropriate therapeutic modalities were used based on grading and staging of the malignancies. Conclusion: This case series highlights the clinical heterogeneity of endometrioid endometrial carcinoma. Increased education regarding early screening measures of endometrial carcinoma will aid in optimizing prevention and treatment protocols.